DIGITALISASI AKUNTANSI PENGELOLAAN KEUANGAN DENGAN METODE ACCRUAL BASIS PADA KLINIK AS SHIFA KENDAL - miftah miftah; Febri Sukmawati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The purpose of this study is to implement the digitization of accounting through the adoption of financial management accounting information systems. Accounting digitalization is needed for automated financial transaction management and results in a fast, accurate, and transparent reporting system. The approach used in building financial management accounting information systems is the accrual basis method, the research method used is the method of research and development (R&D) with a prototype system development model. The results of this study indicate that the digitalization of accounting by implementing financial management information systems at As shifa clinics shows that the information system can work as expected and is able to meet needs. Based on the results of testing the effectiveness of the old system compared to the new system it can be concluded that the performance of financial management in the As Shifa clinic using the new system is more effective than using the old system.